CRITICAL THINKING AMONG SENIOR HIGH SCHOOL STUDENTS ON HOAX INFORMATION IN SOCIAL MEDIA - Urin Laila Sa’adah; Blasius Boli Lasan; Nur Hidayah (Jurnal Pendidikan Humaniora, 2020)
Abstract: Hoax information which is shared in social media has a negative impact to social media users, students in this case are such to be high category users, so it is very risk to face a hoax information impacts. This research & development (R&D) uses Butterworth and Thwaites theory, that is developed to be a modul for high school students and be a guide books for teachers as counselling media at school. Through 9 steps, adjusted from 10 steps of Borg and Gall models, the result of this research is a critical thinking modul for hoax information at social media to the senior high school students and a guide book of a critical thinking modul for hoax information at social media to the senior high school students for the teachers, through effectiveness test.Keywords: critical thinking, social media, hoax, information, studentAbstrak: Informasi hoaks yang tersebar melalui media sosial memberikan dampak buruk bagi penggunanya, pelajar dalam hal ini masuk kategori tinggi sebagai pengguna media sosial, sehingga rawan terpapar dampak informasi hoaks. Penelitian dan pengembangan ini menggunakan teori berpikir kritis Butterworth dan Thwaites yang dikembangkan menjadi modul bagi siswa tingkat SMA dan buku panduan bagi guru BK sebagai media bimbingan di sekolah. Melalui 9 tahapan, yang telah disesuaikan dari 10 tahapan model Borg dan Gall, Hasil dari penelitian ini menghasilkan modul berpikir kritis atas informasi hoaks di media sosial bagi siswa tingkat SMA dan buku panduan atas modul berpikir kritis atas informasi hoaks di media sosial bagi siswa tingkat SMA yang diperuntukkan bagi guru BK, melalui uji efektifitas.Kata kunci: berpikir kritis, media sosial, hoaks, informasi, siswa